Protocol of a mixed (Retrospective and Prospective) longitudinal observational study of amiodarone for chronic Chagas cardiomyopathy (AMIO-CHAGAS study): Investigating immunomodulatory and trypanocidal effects - Juliana Magalhães Chaves Barbosa; Amanda Faier-Pereira; Alejandro Marcel Hasslocher-Moreno; Andréa Rodrigues Costa; Evelyn Nunes Goulart da Silva Pereira; Fernanda de Souza Nogueira Sardinha Mendes; Gilberto Marcelo Sperandio da Silva; Luiz Henrique Conde Sangenis; Marcelo Teixeira Holanda; Mauro Felippe Felix Mediano; Roberto Magalhães Saraiva; Sérgio Salles Xavier; et al. (PLoS ONE, 2026)
Background Chronic Chagas cardiomyopathy (CCC) is the most significant clinical manifestation of Chagas disease (CD) due to its impact on morbidity and mortality. Cardiac manifestations include dilated cardiomyopathy, with ventricular dysfunction, heart failure, cardiac arrhythmias and cardioembolic events. Amiodarone (AMIO) is the most commonly used antiarrhythmic drug in CCC primarily prescribed for patients with severe conduction system abnormalities. Despite preliminary evidence, no clinical study has specifically evaluated the immunomodulatory and trypanocidal effects of AMIO in patients with CCC. The main objective is to evaluate the association of AMIO therapy with serological reactivity to anti- T. cruzi and the inflammatory profile of patients with CCC. Methods/Design This is a mixed (retrospective and prospective) longitudinal observational study enrolling 90 patients who will be recruited from a reference center for CD in Brazil. Patients with CCC receiving AMIO will be compared with those not receiving the drug. AMIO was prescribed at the discretion of the treating physician, independently of the present study. Eligible participants will be invited to participate during routine medical appointments. Clinical data, including electrocardiographic and echocardiographic parameters obtained during routine follow-up, will be retrospectively extracted from medical records. Blood samples will be collected at predetermined time points. The primary endpoint will be the inflammatory profile and serological reactivity to anti- T. cruzi in CCC patients. Secondary endpoints will include: ( 1 ) cardiovascular events; ( 2 ) CCC progression; ( 3 ) implantable cardioverter-defibrillator (ICD) implantation; ( 4 ) heart transplantation; ( 5 ) all-cause death and ( 6 ) a composite endpoint. The association between AMIO use and longitudinal changes in continuous variables will be determined using mixed linear models. Cox regression analysis will be used to investigate the relationship between AMIO use and selected outcomes (cardiovascular events, CCC progression, and death), adjusted for potential confounders. Hazard ratios (HRs) with 95% confidence intervals (CIs) will be reported. Discussion Given the limited literature on the potential trypanocidal and immunomodulatory effects of AMIO in CCC, the findings of this study may provide new insights into the therapeutic potential of AMIO beyond its established antiarrhythmic properties.